Upaya Pelestarian Budaya Melalui Dokumentasi Budaya Desa Baobolak Kecamatan Nagawutung, Kabupaten Lembata - Fransiskus Riberu; Meylisa Yuliastuti Sahan; Maria Florencia Yunita Bello (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
Culture is an integral part of human life that cannot be separated from daily activities. As cultured beings, human beings have a responsibility to preserve cultural heritage so that it is still understood, lived and understood by the next generation. Baobolak village, which is located in Nagawutung District, Lembata Regency, is one of the areas with Lamaholot ethnic communities that are rich in various cultures, both in the form of object and intangible culture. However, with the Times and the flow of modernization, some local cultural values began to erode and potentially forgotten by the younger generation. In an effort to preserve the culture, an effective method is needed to maintain the existence and reintroduce local culture to the wider community. One of the methods considered relevant is through cultural documentation. This study aims to document the various forms of Culture found in the village of Baobolak, both in aspects of history, tradition, and social values of the local community. The methods used in this study include semi-structured interviews, field observations, and audiovisual documentation. The result of the research is a documentary film that comprehensively describes the cultural and historical life of Baobolak Village. To measure the success rate of the documentary product, researchers conducted a survey of the younger generation in the village. Based on the survey results, as many as 81% of 21 respondents stated that they understand and re-live the culture and history of Baobolak village after watching the documentary. Thus, cultural documentation through the medium of film has proven effective as a means of cultural preservation and education for the younger generation in the midst of increasingly rapid social change